The Use of Battered Woman Syndrome in U.S. Criminal Courts - Holliday, Jessica R.; McNiel, Dale E.; Morris, Nathaniel P.; Faigman, David L.; Binder, Renée L. (Journal of the American Academy of Psychiatry and the Law Online, 2022)
Although not recognized by any edition of the Diagnostic and Statistical Manual of Mental Disorders, battered woman syndrome (BWS) has been offered as a defense in U.S. criminal courts for several decades. This article reviews examples of criminal cases in which BWS has been used in the United States as well as the implications of BWS for the practice of forensic psychiatry. Historically raised in cases of self-defense, BWS has also been used in criminal defenses involving duress, as well as by prosecutors to explain witness recantations. Case law suggests that expert witness testimony on BWS is often admissible in jurisdictions across the United States, yet its use in criminal defenses has received mixed responses from various courts. We examine limitations on the use of BWS in criminal courts and the potential use of posttraumatic stress disorder as an alternative and more reliable diagnosis in similar legal contexts.